The experience of volunteer witnesses for Medical Assistance in Dying (MAiD) requests. Issue 1 (2nd January 2022) - Praslickova, Zuzana; Kelly, Michaela; Wiebe, Ellen
Abstract: Many jurisdictions with legal forms of assisted dying require that written requests be witnessed by independent witnesses. In Canada, a unique program of volunteers was founded to make such witnesses available. A total of 106 volunteers completed a questionnaire about their experiences, challenges, and perspectives; 24 were also interviewed. Although the witnesses felt well prepared for their roles, they encountered challenges including role uncertainty, communication difficulties, and the emotional impacts of being with suffering patients and their grieving families. Most felt that the requirement for independent witnesses is an intrusive and unnecessary barrier to accessing medical assistance in dying.